2021
DOI: 10.3390/genes12030340
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure Analysis of Triticum aestivum L. Landrace Panel from Afghanistan

Abstract: Landraces are a potential source of genetic diversity and provide useful genetic resources to cope with the current and future challenges in crop breeding. Afghanistan is located close to the centre of origin of hexaploid wheat. Therefore, understanding the population structure and genetic diversity of Afghan wheat landraces is of enormous importance in breeding programmes for the development of high-yielding cultivars as well as broadening the genetic base of bread wheat. Here, a panel of 363 bread wheat land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
3
11
1
Order By: Relevance
“…Even though the final datasets were significantly reduced, high-quality SNP markers have remained widely distributed abroad the three genomes, as shown in Supplementary Table S2. Genome D and the homoeologous chromosomes of the fourth group were characterized by the lowest number of markers; this result is in accordance with those of other authors [22][23][24] who analyzed Spanish, Iranian, and Afghan common wheat landraces with the same DArTseq approach. The limited diversity of D genome may be originated from the "recent" introgression occurred with Aegilops tauschii (2n = DD), the common wheat D-genome donor, and the relative genetic bottleneck [27].…”
Section: Population Structure Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Even though the final datasets were significantly reduced, high-quality SNP markers have remained widely distributed abroad the three genomes, as shown in Supplementary Table S2. Genome D and the homoeologous chromosomes of the fourth group were characterized by the lowest number of markers; this result is in accordance with those of other authors [22][23][24] who analyzed Spanish, Iranian, and Afghan common wheat landraces with the same DArTseq approach. The limited diversity of D genome may be originated from the "recent" introgression occurred with Aegilops tauschii (2n = DD), the common wheat D-genome donor, and the relative genetic bottleneck [27].…”
Section: Population Structure Analysissupporting
confidence: 91%
“…Recent works in this field demonstrated how geography was the main effect driving the genetic diversity [22,24], even though others did not find any geographical effect on genetics [20,23]. In this study, β-coefficients, calculated by MLR, clearly demonstrated how a geographic effect existed between Clu1 and Clu2.…”
Section: Population Structure Analysismentioning
confidence: 50%
See 1 more Smart Citation
“…The understanding of the population structure is crucial for further downstream analysis, for example, genome-wide association studies (GWAS). The evaluation of genetic diversity also provides vital information which can help in the preservation strategies and broadening of the genetic base of crops ( Eltaher et al, 2018 ; Tehseen et al, 2021a ). The presence of subpopulations in the panel can be attributed to the selection of desirable traits and genetic drift ( Kumar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fixation index (Fst) is used to measure the genetic differentiation among the populations ( Tehseen et al, 2021a ). An Fst value of 0.15 and more predicts the presence of a significant genetic differentiation in the subpopulations ( Frankham et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%